ELLIPSIS OF SUBJECT IN BALINESE SUBORDINATIVE CONSTRUCTION - Mandra, I Wayan Mandra (e-Journal of Linguistics; Vol. 7. Juli 2013 No. 2)
This study was aimed at identifying the types of constructions in which ellipsis of subject took place in the Balinese language, the meaning of conjunction, and the syntactic category of the omitted subject in Subordinative construction. Descriptive-qualitative method was used, and the ellipsis of subject in the Balinese Subordinative construction was investigated in the present study. The data were collected using triangulation system, that is, the combined method of observation, interview, and documentation. From the process of observation, the researchers noted down the Subordinative constructions in which the ellipsis of subject took place. Then the data were selected based on the meaning of the conjunction used. The data were taken from a Balinese story. The data which could not be obtained from the written source were replaced by the intuitive data as the researcher is a Balinese native speaker. To make the intuitive data more accurate, the informants who were knowledgeable of the structures of the written and spoken Balinese language were used. The result of the study showed that the conjunctions used in the Subordinative constructions indicated temporal, expectation, concession, cause, result, conditional, and unison meaning relations. Furthermore, it was identified that the constituents in which the ellipsis of subject took place in the Subordinative constructions were noun, noun phrase, and pronoun (the first and third pronouns).
Keywords: Ellipsis of subject, meaning of conjunction, and syntactic category